High-Precision Dual-Loop Position Control of an Asymmetric Bilateral Linear Hybrid Switched Reluctance Motor - Pan, J. F.; Zou, Yu; Cao, Guangzhong; Cheung, Norbert C.; Zhang, Bo (IEEE transactions on magnetics, 2015)
In this paper, to enhance the machine performance and realize a high-precision position control performance, a dual-loop position controller is employed for the asymmetric bilateral linear hybrid switched reluctance motor (ABLHSRM). Machine characteristics are investigated by finite-element method. The dual-loop controller is constructed by employing a tradition proportional-integral differential velocity controller as the inner loop and a fuzzy proportional differential (PD) controller for the outer loop. Experimental results demonstrate that both the position control performance and the velocity control performance under the dual-loop control algorithm are superior to the single-loop PD position control strategy. An absolute steady-state error of 4 μm can be achieved under the dual-loop control strategy. Performance comparison from the ABLHSRM and its asymmetric bilateral linear switched reluctance counterpart with the same dimensions are carried out. Position tracking results show that the rise time is improved for the proposed ABLHSRM under the proposed control scheme.